Perlindungan Hukum terhadap Lagu yang Dilaporkan Melanggar Hak Cipta di Situs Youtube - Nihayati, Wafa; Sakundiana, Vita Dwi; Alatas, Lulu Syakirah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Currently, many YouTube users upload song-related videos, such as lyric videos or cover versions of songs, which involve re-performing songs owned by others. A common issue that arises is that these users often upload such song videos on YouTube without obtaining permission from the original songwriter, and in many cases, the videos are uploaded for commercial purposes. The purpose of this research is to understand the legal protection of songs reported for copyright infringement on YouTube. The research method used is normative juridical, which focuses on viewing law as a normative discipline. This is conducted through literature studies, especially secondary data such as legislation, court decisions, contractual agreements, or other legal documents, supported by relevant literature related to the researched issue. Based on Article 9 paragraph (2) of the Indonesian Copyright Law, it is stated that anyone is prohibited from using or reproducing a creator’s work for commercial purposes without permission. This implies that the act of re-uploading or including a music video/song that is not their own original creation for the purpose of their video constitutes a copyright infringement. In the case of a content creator using someone else's work, this action is categorized as a violation under Article 113 paragraph (2) of the Copyright Law (UUHC), particularly if the content creator engages in the actions described in Article 9 paragraph (1) points c, d, f, and h for commercial purposes. They may be subject to a criminal penalty of up to 3 years in prison or a fine of up to 500 million Rupiah.